2012
DOI: 10.1186/bcr3162
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the vitamin D pathway, serum levels of vitamin D, and estrogen receptor negative breast cancer among African-American women: a case-control study

Abstract: IntroductionAmerican women of African ancestry (AA) are more likely than European Americans (EA) to have estrogen receptor (ER)-negative breast cancer. 25-hydroxyvitamin D (25OHD) is low in AAs, and was associated with ER-negative tumors in EAs. We hypothesized that racial differences in 25OHD levels, as well as in inherited genetic variations, may contribute, in part, to the differences in tumor characteristics.MethodsIn a case (n = 928)-control (n = 843) study of breast cancer in AA and EA women, we measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…The lack of consistency of the associations in AA and EA women is not unexpected. In the WCHS, we previously found that genetic associations in several biological pathways, including several vitamin D‐related genes, differed between AA and EA women. These data suggest that associations between genetic variants in vitamin D‐related pathways and breast cancer risk in AAs may be different from those in EAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of consistency of the associations in AA and EA women is not unexpected. In the WCHS, we previously found that genetic associations in several biological pathways, including several vitamin D‐related genes, differed between AA and EA women. These data suggest that associations between genetic variants in vitamin D‐related pathways and breast cancer risk in AAs may be different from those in EAs.…”
Section: Discussionmentioning
confidence: 99%
“…AAs have a high rate of vitamin D deficiency, likely due, in part, to dark skin pigmentation which blocks UVB light, and, to a lesser extent, lactose intolerance which may limit vitamin D intake from fortified dairy products . Our previous studies have also demonstrated wide‐spread differences in variant frequency and linkage disequilibrium (LD) in vitamin D‐related genes between AA and EA populations . It is thus important to understand whether ancestral variations in vitamin D‐related genes in AAs, which were shaped over millennia in sun exposure‐abundant Africa, would put AA women at high risk of breast cancer in a Northern hemisphere environment where sun exposure is limited and seasonally fluctuates …”
mentioning
confidence: 99%
“…The Women's Circle of Health Study (WCHS), a case–control study designed to evaluate risk factors for aggressive breast cancer in AA women, was conducted in the metropolitan New York City area and seven counties in New Jersey and has been previously described in detail . Eligible participants included English‐speaking AA and EA women ages 20 to 75 years, with no previous history of cancer other than non‐melanoma skin cancer, who were diagnosed with primary, histologically confirmed breast cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of single nucleotide polymorphisms (SNPs) in GC found no significant association with breast cancer risk [25,28,29]. CYP27B1 and CYP24A1 are involved in the activation and degradation of 25(OH)D and 1,25(OH) 2 D. Only five studies examined the association between SNPs on these genes and breast cancer risk [25,2831]. A review suggests that some SNPs on these genes may be associated with breast cancer risk, but results are inconclusive [32].…”
Section: Introductionmentioning
confidence: 99%